The influence of co-sponsorship on MPs' agenda-setting success. Issue 2 (23rd February 2021) - Sciarini, Pascal; Fischer, Manuel; Gava, Roy; Varone, Frédéric
Abstract: This study investigates the influence of MPs' co-sponsorship activities on their agenda-setting success. It analyses the strategic choices open to MPs who engage in co-sponsorship, the resulting centralities in the co-sponsorship network, and the effects on the success of parliamentary proposals. MPs can develop their co-sponsorship efforts within their party family ('bonding') or beyond it ('bridging'), and they can use co-sponsorship both to receive political support ('support-seeking') and to provide it ('support-providing'). The success of these different co-sponsorship strategies is empirically assessed here by investigating the acceptance or refusal of parliamentary proposals introduced in the Swiss Parliament from 2003 to 2015. The bridging/support-seeking strategy that pro-actively recruits co-sponsors across party families is the most rewarding. This holds especially for MPs belonging to pole parties, who overall appear as more sensitive to centrality-related effects than MPs of moderate right parties.